PENGARUH FINANCIAL DISTRESS, PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN, DAN REPUTASI AUDITOR TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Industri Pariwisata dan Rekreasi Yang Terdaftar di BEI Tahun 2020-2021) - Rosali, Tiara Paramitalynia; Fachriyah, Nurul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to examine the effect of financial distress, profitability, solvability, firm size, and auditor reputation on the audit report lag of Tourism and Recreation industry companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2021 observation period. The samples include 60 data according to the criteria from 30 companies, selected through purposive sampling. The data of financial statements are analyzed quantitatively by multiple linear regression utilizing SPSS 25 software. The results of this study exhibit that financial distress has a positive effect on audit report lag; profitability has a negative effect on audit report lag; and solvability, firm size, and auditor reputation have no effect on audit report lag.